Mango Growers’ Preference of Mango Varieties According to Profitability in Murshidabad District - Tanushree Saha,; Sagar Mondal, Madhurima Maiti, (Indian Journal of Extension Education, 2022)
Murshidabad district is famous for mango cultivation and presently around two hundred traditional mango varieties are produced. The present study was conducted on eighty mango growers randomly selected from five villages under Farakka block of Murshidabad district in May, 2021. The objective of the study was to identify some important mango varieties grown by mango growers and also to find out the relative preferences of the varieties according to profitability. Five varieties of mango namely, Himsagar, Langra, Amrapali, Fazli and Gopalbhog were identified and presented to the respondent in ten pairs. The respondents were asked to select one variety of mango over the other from each pair separately which they consider more profitable. For analysis of data, the method of pair comparisons was followed. According to the perception of the mango growers the most profitable mango variety was Langra followed by Himsagar. Fazli was more profitable than Amrapali but Gopalbhog was least profitable as perceived by the mango growers.